Handheld device formfactor effects on worker productivity during loading tasks: a case study. (14th June 2022) - Burch, Reuben; Strawderman, Lesley; Ross, Tyler; Bian, Linkan; King, Katherine; Babski-Reeves, Kari; Nur, Farjana
With the high number of boxed products processed at material handling and product distribution hubs, reducing scanning time and errors are key to improving operations. This study identifies the impact of select scanning technology on worker productivity, error rate, and perceived usability during simulated scanning tasks. A large material handling company selected five scanning device formfactors for device procurement evaluation during a request for purchase process. Productivity, error rate, and usability were assessed by 37 participants for each device during the replication of an aircraft container loading task. The average scanning time was lowest for wand and ring scanners (0.161, 0.162 minutes) and highest for the smartphone (0.256). The average error rate was lowest for the wand scanner (1.29%) and highest for the smartphone (3.84%). The average usability score was highest for ring and wand scanners (47.19, 47.95) and lowest for the smartphone (25.19). Superior performances from wand and ring scanners are likely due to simple design and effective feedback, with results indicating they should be used as primary scanning devices for highly repetitive material handling tasks.